Parametric analysis of the liquid-state objects images obtained by gas discharge visualization method - L.D. Pysarenko; A.B. Zavgorodniy (Журнал нано- та електронної фізики)
Analysis of the parametric methods for the liquid-state objects images estimation obtained by gas discharge visualization (GDV) method was done. New quantitative parameters for geometric and fractal properties of GDV-grams determination was offered. Modified algorithm for their calculation was shown.